Circadian variations in the pharmacokinetics of bucinnazine in rats. Issue 5 (3rd July 2020) - Yu, Zaoqin; Li, Xiping; Feng, Chengyang; Lei, Kai; He, Wenxi; Zhang, Chengliang; Liu, Dong
ABSTRACT: Circadian rhythms play crucial roles in the action and pharmacokinetics of a drug. The processes from drug absorption to excretion, which participate in pharmacokinetic steps, are circadian time-dependent. Our previous study has demonstrated that the analgesic effect of bucinnazine, an anesthetic analgesic drug, revealed significant circadian variation. In the current study, we aimed to investigate the effect of different administration time on the pharmacokinetic process of bucinnazine in rats. Male Sprague Dawley rats were randomly divided into 9:00 am and 9:00 pm groups. Blood samples (0.4 ml) were, respectively, collected at 0, 0.033, 0.083, 0.17, 0.33, 0.67, 1, 1.5, 2, 3, 4, 6, and 8 h after intraperitoneal injection of 20 mg/kg bucinnazine and determined using the established liquid chromatography-tandem mass spectrometry method. DAS 2.0 was used to calculate the pharmacokinetic parameters. The pharmacokinetics of bucinnazine exhibited significant circadian-time dependence. AUC and Cmax of bucinnazine increased significantly at 9:00 am compared with that at 9:00 pm ( P < 0.05), while Tmax was significantly decreased at 9:00 am than at 9:00 pm ( P < 0.05). Pharmacokinetic processes of bucinnazine significantly varied along with administration time, indicating that attention should be paid to the time in clinical practice to improve analgesic effects and to decrease adverse reactions.